2015
DOI: 10.4236/ojopm.2015.52004
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microspheres Based on Poly(4-butyltriphenylamine) Blends with Poly(methyl methacrylate) and Block Copolymer by Solvent Evaporation Method

Abstract: Micron-sized polymer particles from single poly(4-butyltriphenylamine) (PBTPA) homopolymer, binary polymer blend [PBTPA/poly(methyl methacrylate) (PMMA)], and ternary polymer blend (PBTPA/PBTPA-b-PMMA/PMMA) via a solvent evaporation method, and the surface morphologies and inside structure of resulting particles were investigated. Spherical homopolymer particles with smooth surface were resulted from PBTPA with low molecular weight. In the case of binary blends (PBTPA/PMMA = 1/1), Janus (low molecular weight) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Our research group previously reported the fabrication of microspheres consisting of blend of poly(4-butyltriphenylamine) (PBTPA) and poly(methyl methacrylate) (PMMA) via the solvent evaporation method and investigated the effect of molecular weight of PBTPA on the morphology [ 13 ]. PBTPA has a semi-conjugated structure in which 4-butyltriphenylamine units are directly linked together and exhibits excellent hole-transporting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group previously reported the fabrication of microspheres consisting of blend of poly(4-butyltriphenylamine) (PBTPA) and poly(methyl methacrylate) (PMMA) via the solvent evaporation method and investigated the effect of molecular weight of PBTPA on the morphology [ 13 ]. PBTPA has a semi-conjugated structure in which 4-butyltriphenylamine units are directly linked together and exhibits excellent hole-transporting properties.…”
Section: Introductionmentioning
confidence: 99%